2019
DOI: 10.1016/j.maturitas.2018.11.003
|View full text |Cite
|
Sign up to set email alerts
|

The health economics burden of sarcopenia: a systematic review

Abstract: Despite of better knowledge about sarcopenia, an optimal understanding of its consequences from a public health perspective remains a challenge. Specifically, the economic burden of the illness is unclear. As a support for the public health policy makers and other health actors, our objective was to perform a systematic review of the literature comparing healthcare costs between sarcopenic and non-sarcopenic patients (under the registration number CRD42018099291). A search for relevant articles was conducted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
102
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(113 citation statements)
references
References 42 publications
(122 reference statements)
0
102
0
1
Order By: Relevance
“…Sarcopeniathe degeneration of muscle mass combined with loss of muscle function due to aging 1 has become a public health matter. 2 The multiple adverse health outcomes associated with low muscle mass (fractures and falls, [3][4][5][6][7] insulin resistance and the risk of prediabetes, 8,9 cardiovascular diseases, 10 cognitive impairment, 11 depression 12 and others 13 ), the impact of sarcopenia on the individual's life (loss of independence, 14 reduced quality of life, 12,15,16 earlier necessary admission to nursing homes 14,17 ) and the resulting socioeconomic burden [18][19][20] have made the necessity for interventions clear. Many studies have already proven the positive effects of resistance training (RT) combined with a protein-rich diet on sarcopenia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sarcopeniathe degeneration of muscle mass combined with loss of muscle function due to aging 1 has become a public health matter. 2 The multiple adverse health outcomes associated with low muscle mass (fractures and falls, [3][4][5][6][7] insulin resistance and the risk of prediabetes, 8,9 cardiovascular diseases, 10 cognitive impairment, 11 depression 12 and others 13 ), the impact of sarcopenia on the individual's life (loss of independence, 14 reduced quality of life, 12,15,16 earlier necessary admission to nursing homes 14,17 ) and the resulting socioeconomic burden [18][19][20] have made the necessity for interventions clear. Many studies have already proven the positive effects of resistance training (RT) combined with a protein-rich diet on sarcopenia.…”
Section: Introductionmentioning
confidence: 99%
“…The training should be time-efficient, considering reasons for abstaining from recommended exercise doses have been time restriction and little enthusiasm 27,28 and cost-efficient in the face of the high and growing prevalence of sarcopenia 29 and the resulting financial burden for stakeholders. 18,19,[30][31][32] A training modality meeting these criteria is high-intensity resistance training (HI-RT), a single-set resistance training at an intensity of load at 70-85% of the one-repetition maximum (1RM). 33 To have a maximum effect on muscle strength and mass and also parameters like bone density 34,35 and hormonal levels, 36 relative intensity of 70% RM and up is needed, which falls in the range of HI-RT.…”
Section: Introductionmentioning
confidence: 99%
“…Musculoskeletal disorders are common among older people and are a leading cause of morbidity worldwide [1]. Sarcopenia, the loss of muscle mass and strength with age, is associated with increased risk of disability and mortality and significant healthcare costs [2][3][4]. Annual direct medical costs attributable to sarcopenia were estimated at $18.5 billion in the United States in 2000 [5] and annual excess health and social care costs associated with muscle weakness were estimated at £2.5 billion in a recent UK study [6].…”
Section: Introductionmentioning
confidence: 99%
“…These numbers are expected to increase with the aging of the population and the concomitant rise in the prevalence of sarcopenia. A recent systematic review indeed found higher healthcare costs for patients with sarcopenia, but concluded that more research should be conducted to assess the true impact of sarcopenia on healthcare consumption [ 17 ].…”
Section: Introductionmentioning
confidence: 99%